Consistency of the Presidential System in Indonesia - Kuswanto Kuswanto (Sriwijaya Law Review, 2018)
The current presidential system in Indonesia is the result of the amendments of the 1945 Constitution. Prior to Indonesian reform, the presidential system was influenced by a strong parliamentary pattern in which the president was responsible for the People's Consultative Assembly. Today, this provision is no longer exist. However, consistency of the presidential system is still problematic because the the dominance power of the president over the House of Representatives. These problematic points are not in line with presidential system principle because it reduce the authority of president. The Parliament may only establish any law as long as it is pursuant to the 1945 Constitution. This article aims to examine the issue of the Indonesian presidential system at least in two following sections. Firstly, it deals with dominance of presidential power over the House of Representatives. Secondly, president establishes the independent bodies such as Corruption Eraditation Commission (KPK) and National Commission of Human Rights (Komnas HAM) which are constitutionally less restricted.